In Vitro Evaluation of Antimicrobial Efficacy of Extracts Obtained from Raw and Fermented Wild Macrofungus, Lenzites quercina - Olusola Clement Ogidi; Victor Olusegun Oyetayo; Bamidele Juliet Akinyele (International Journal of Microbiology, 2015)
In recent time, there is a major concern about antibiotic resistance displayed by some pathogenic microorganisms and this had involved a continuous search for natural antimicrobial products. The phytochemistry as well as antimicrobial activity of extracts obtained from Lenzites quercina was investigated. The extracts and purified fractions were, respectively, tested against indicator organisms using agar well diffusion and disc diffusion methods. The quantity of phytochemicals found in the extracts of L. quercina ranged from 14.4 to 20.7 mg/g for alkaloids, 6.1 to 12.8 mg/g for steroids, 4.5 to 10.6 mg/g for saponins, 2.8 to 17.2 mg/g for terpenoids, and 0.41 to 17.1 mg/g for flavonoids. The gas chromatography mass spectrophotometry (GCMS) analysis of the extract reveals the presence of caprylic acid, stearic acid, tetradecanoic acid, methyl-11-octadecenoate, oleic acid, and 4-methyl-2-propyl-1-pentanol. Extracts of L. quercina and its purified fractions exhibited wider range of inhibition (4 mm to 26 mm) on Staphylococcus aureus (ATCC 29213), Pseudomonas aeruginosa (ATCC 27853), Escherichia coli (ATCC 35218), Methicillin Resistant Staphylococcus aureus (MRSA), Salmonella typhi, Bacillus cereus, Enterococcus faecalis, Candida albicans, and Aspergillus niger. The antimicrobial effects of L. quercina extracts indicate that this wild macrofungus contains significant amount of pharmacological agents, which could be extracted to curb the menace of antibiotic resistances by pathogenic organisms.